Improving Treatment Performance of Dissolved Air Flotation System by Using Ionic Liquids as Surfactants - Mohammed, Sawsan A.M.; Fadhil, Aws Abbas (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The effect of three ionic liquids viz., 1-hexyl-3-methylimidazolium tetrafluoroborate (ILE), 1-hexyl-3-metylimidazolium hexafluorophosphate (ILF) and 1-octyl-3-methylimidazolium tetrafluoroborate (ILG) when used as surfactants on the performance of dissolved air floatation (DAF) was investigated. Experiments were conducted at a temperature of 30-35 ºC, 10ppm ferric chloride as coagulant, 50% recycle ratio, pH 8, and 10 minutes treatment time to find oil and grease (OG) and turbidity removal efficiencies at saturation pressure (2-6) bar. ILs were used at concentration of 50 µl/liter of treated water in two positions in DAF system; the saturation vessel and the treatment tank. The performance using ILs in the saturation vessel were better than that in treatment tank because ILs reduced the surface tension of water, which lead to an increase in the solubility of air in water and eventually increase the microbubble formation. The OG removal efficiency using ILG as an efficient surfactant in saturation vessel was higher than that in the treatment tank and higher than other ILs (ILG>ILF>ILE). The removal efficiency reached about 90% at a saturation pressure of 5 bar, and 85% at 3 bar, which reduces the operation costs. The treated water oil concentration at 3bar was 9.5 ppm, which meets the Iraqi pre-disposal regulatory limit.